The Role of Irrational Beliefs, Self Efficacy and Social Support in Relapse of Abuse Disorder - Toraj Hashemi; Sakineh Fotuhie-Bonab; Hamidreza karimi, H; Mansour Bayrami (Drug Control Headquarters, Research and Education Office, 2010)
Aim: This study aimed to determine the role of irrational beliefs system, self efficacy and social support network in predicting of relapse/non-relapse of drug misusing, and comparison of mentioned variables between these two groups. Method: For this purpose 100 persons who had repeated relapse and 100 persons who did not have relapse were selected by available sampling of Rehabilitation Organization of Tabriz city. Albert Alic's irrational beliefs, Sherer's self efficacy and Wax's social support questionnaires administered among selected samples. Results: The results showed that, there were significant differences between two relapse and non-relapse groups on irrational beliefs, self-efficacy and social support. Conclusion: The results have applied implications in addiction treatment clinics.